Improvement of productivity by applying Poka Yoke, SMED and TPM in a SME in the brick production sector - Becerra-Flores, Alonso Arturo; Salas-Sotelo, Jhonny Sergio Wildo; Corzo-Chavez, Jorge Antonio (LACCEI, 2024)
By the end of 2022, the construction sector in Peru had experienced a growth of 6.02%, consequently benefiting the brick industry as well. This research focuses on studying a small and medium-sized enterprise (SME) facing productivity challenges that compromise its profitability and competitiveness.​ Periodic visits were conducted to the company to gather data. The main issues were identified using a Pareto diagram, including excessive production time, human error, unplanned machinery downtime, and reprocessing, with the first three being the most remarkable. Root causes of each problem were identified to link them to solutions based on Lean Manufacturing principles, such as TPM, SMED, Poka Yoke and activity standardization. Improvement proposals were suggested and validated through simulation in Arena, yielding positive results, such as a 7-hour reduction in total production time, a 40% decrease in setup times, a 2% reduction in defective products, and a 75% decrease in the incidence of human errors in some activities, such as mixing. Finally, the profitability of the proposal was evaluated, resulting in a Net Present Value (NPV) of $ 58,259, an Internal Rate of Return (IRR) of almost 30% and a Payback Period of 3 months.